2006
DOI: 10.1002/ptr.1843
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the Chinese herbal medicine formula STA‐1 in the treatment of allergic asthma

Abstract: Although some formulae of traditional Chinese medicines (TCM) have been used for antiasthma treatment, few of them have had sufficient discussion on their efficacy, safety and mechanisms. In this study, the availability of the TCM formula STA-1 for the treatment of allergic asthma was investigated by conducting a double-blind, placebo-controlled and randomized trial. One hundred and twenty patients between the ages of 5 to 20 years with mild-to-moderate asthma were included. These patients were treated with ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 22 publications
0
55
0
3
Order By: Relevance
“…Twenty-eight patients were assigned to the treatment group and 24 to the placebo group. At the end of the treatment period, AHR determined by log PC (20) was significantly improved in the DCT group (0.51 +/-1.05 mg/ml vs. 0.26 +/-0.84 mg/ml, p = 0.034). The clinical and medication scores showed improvement in the DCT group (p = 0.004).…”
Section: Ding Chuan Tangmentioning
confidence: 94%
See 1 more Smart Citation
“…Twenty-eight patients were assigned to the treatment group and 24 to the placebo group. At the end of the treatment period, AHR determined by log PC (20) was significantly improved in the DCT group (0.51 +/-1.05 mg/ml vs. 0.26 +/-0.84 mg/ml, p = 0.034). The clinical and medication scores showed improvement in the DCT group (p = 0.004).…”
Section: Ding Chuan Tangmentioning
confidence: 94%
“…In 2006, Chang et al [20] reported results of a clinical evaluation of the Chinese herbal medicine formula STA-1 containing 10 herbs [ Table 1] and STA-2 in the treatment of allergic asthma in a double-blind, placebo-controlled, randomized trial. STA-1 is a combination of mMMDT and Lui-Wei-Di-Huang Wan (LWDHW).…”
Section: Sta-1mentioning
confidence: 99%
“…Twenty-eight patients were assigned to the treatment group and 24 to the placebo group. At the end of the treatment period, AHR determined by log PC (20) was significantly improved in the DCT group (0.51 +/− 1.05 mg/ml vs. 0.26 +/− 0.84 mg/ml, p = 0.034). Clinical and medication scores showed improvement in the DCT group (p = 0.004).…”
Section: Ding Chuan Tang (Dct)mentioning
confidence: 94%
“…Chang et al (20) reported results of a clinical evaluation of STA-1 and STA-2 herbal formulas [ Table 1]. STA-1 and STA2-2 are combinations of mMMDT (10 herbs) and LuiWei-Di-Huang Wan (LWDHW, 6 herbs).…”
Section: Sta-1mentioning
confidence: 99%
“…Recently, TCM has been attracting interest in Western countries as a source of alternative or complementary therapy for a variety of diseases, including allergies and asthma. [4][5][6][7][8] FAHF-2 is the first botanical investigational new drug (IND) approved for clinical studies for food allergy by the US Food and Drug Administration (FDA). FAHF-2 is a 9-herb formula based on the classical Chinese herbal formula Wu Mei Wan.…”
Section: Introductionmentioning
confidence: 99%